2022
DOI: 10.1093/cid/ciac312
|View full text |Cite
|
Sign up to set email alerts
|

Favipiravir for Treatment of Outpatients With Asymptomatic or Uncomplicated Coronavirus Disease 2019: A Double-Blind, Randomized, Placebo-Controlled, Phase 2 Trial

Abstract: Background Favipiravir is an oral, RNA-dependent RNA polymerase inhibitor with in vitro activity against SARS-CoV2. Despite limited data, favipiravir is administered to patients with COVID-19 in several countries. Methods We conducted a phase 2 double-blind randomized controlled outpatient trial of favipiravir in asymptomatic or mildly symptomatic adults with a positive SARS-CoV2 RT-PCR within 72 hours of enrollment. Particip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…The second was a randomized, single-blind, placebo-controlled trial of Peginterferon Lambda-1a (Lambda) for reducing the duration of viral shedding or symptoms [ 19 ] in which oropharyngeal swabs were collected for 28 days after enrollment. The third was a phase 2, double-blind, randomized controlled outpatient trial of the antiviral favipiravir for reducing the duration of viral shedding in which participants self-collected daily anterior nasal swabs for 28 days after enrollment [ 20 ]. Neither Lambda nor favipiravir was found to shorten the duration of SARS-CoV-2 viral shedding [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second was a randomized, single-blind, placebo-controlled trial of Peginterferon Lambda-1a (Lambda) for reducing the duration of viral shedding or symptoms [ 19 ] in which oropharyngeal swabs were collected for 28 days after enrollment. The third was a phase 2, double-blind, randomized controlled outpatient trial of the antiviral favipiravir for reducing the duration of viral shedding in which participants self-collected daily anterior nasal swabs for 28 days after enrollment [ 20 ]. Neither Lambda nor favipiravir was found to shorten the duration of SARS-CoV-2 viral shedding [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The third was a phase 2, double-blind, randomized controlled outpatient trial of the antiviral favipiravir for reducing the duration of viral shedding in which participants self-collected daily anterior nasal swabs for 28 days after enrollment [ 20 ]. Neither Lambda nor favipiravir was found to shorten the duration of SARS-CoV-2 viral shedding [ 19 , 20 ]. The fourth was a study of a noninvasive mask sampling method to quantify SARS-CoV-2 shedding in exhaled breath [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…FPV has since been repurposed to treat SARS-CoV-2 [ 3 , 5 , 25 ]. It was shown to inhibit SARS-CoV-2 in vitro in infected Vero E6 cells [ 11 , 12 , 26 ] and appeared to improve clinical outcomes, control viral progression, and promote viral clearance in numerous clinical studies [ 3 , 4 , 6 , 8 , 9 , 27 , 28 ]; however, the clinical benefit was not clearly demonstrated in some studies [ 29–33 ]. More than 4000 well-characterized patient safety profiles illustrated that effective FPV drug concentrations remained within safe therapeutic dosages [ 6 , 26 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…There were 11 RCTs 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 with adopted evidence. Point estimates were not expected to have a clinically meaningful effect on clinical improvement at 28 days (an increase of 14 per 1,000).…”
Section: Introductionmentioning
confidence: 99%